Analisis manajemen pendidikan karakter di pondok pesantren modern - Achmad Riduansyah; Aslamiah Aslamiah; Muhammad Saleh (Universitas Pendidikan Indonesia, 2026)
Modern Islamic boarding schools (Pesantren) function as total institutions providing 24-hour character education. This qualitative study, employing a multi-site design at MA Darul Hijrah and MA Puteri Annajah, aims to analyze character education management through three focal points: planning, implementation, and monitoring/evaluation. Findings reveal that planning is conducted systematically and participatively through leadership councils, guided by the Panca Jiwa values (sincerity, simplicity, self-reliance, Islamic brotherhood, and freedom). Implementation is carried out through an integrative